High prevalence of poor sleep quality and sleep deficit: A study in children, adolescents, and adult soccer players - Lúcio A. Cunha; Elisa A. Marques; João Brito; Michele Lastella; Pedro Figueiredo (PLoS ONE, 2025)
Objective This observational study aimed to provide insight into the sleep behaviors, chronotypes, and sleep needs of athletes by examining children, adolescents, and adult soccer players from different competitive levels. Methods The study included 864 soccer players (n = 747 males) of various age groups [median age: 17 (interquartile range: 14–20)]. The participants completed an online questionnaire that included demographic questions, the Pittsburgh Sleep Quality Index (PSQI), the Epworth Sleepiness Scale (ESS), the Morningness-Eveningness Questionnaire (MEQ), and a question about their sleep needs. Results Adult players had a higher prevalence of poor sleep quality, excessive daytime sleepiness, and sleep deficit than children and teenagers (p < 0.001). Lower sleep duration was associated with poorer sleep quality and excessive daytime sleepiness (rs = −0.59 to −0.17, p < 0.01). Sleep needs were significantly higher than the habitual sleep duration in teenagers (42 min, p < 0.001) and adult players (41 min, p < 0.001). Players that had poor sleep quality (OR = 3.98, 95% CI: 2.78–5.77), excessive daytime sleepiness (OR = 3.72, 95% CI: 2.32–6.1), evening chronotype (OR = 2.54, 95% CI: 1.48–4.40), and later ending time of training (OR = 1.12, 95% CI: 1.07–1.19) could be at a higher risk of having sleep deficit. Conclusion Nearly half of the adult players had poor sleep quality. Additionally, one-third of the children, and almost half of the teenagers and adult players, had a sleep deficit. Players with poor sleep quality, an evening chronotype, excessive daytime sleepiness, and a later training time might be at a higher risk of experiencing a sleep deficit.